2011
DOI: 10.1186/1471-2350-12-101
|View full text |Cite
|
Sign up to set email alerts
|

Brain tissue- and region-specific abnormalities on volumetric MRI scans in 21 patients with Bardet-Biedl syndrome (BBS)

Abstract: BackgroundBardet-Biedl syndrome (BBS) is a heterogeneous human disorder inherited in an autosomal recessive pattern, and characterized by the primary findings of obesity, polydactyly, hypogonadism, and learning and behavioural problems. BBS mouse models have a neuroanatomical phenotype consisting of third and lateral ventriculomegaly, thinning of the cerebral cortex, and reduction in the size of the corpus striatum and hippocampus. These abnormalities raise the question of whether humans with BBS have a charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 56 publications
5
38
2
Order By: Relevance
“…Though the exact function of cilia in brain development is unclear, expression of genes involved in ciliary transport are seen in developing neural tissues. A recent MRI study investigated the brain in BBS, a ciliopathy that is clinically similar to AS with the exceptions of polydactyly and learning deficits [27]. By means of volumetric analisys, the study disclosed a significant decrease of white matter volume, suggesting a primary white matter involvement in this ciliopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the exact function of cilia in brain development is unclear, expression of genes involved in ciliary transport are seen in developing neural tissues. A recent MRI study investigated the brain in BBS, a ciliopathy that is clinically similar to AS with the exceptions of polydactyly and learning deficits [27]. By means of volumetric analisys, the study disclosed a significant decrease of white matter volume, suggesting a primary white matter involvement in this ciliopathy.…”
Section: Discussionmentioning
confidence: 99%
“…In this region, AS patients had increased mean and radial diffusivity consistent with axonal involvement. It has been demonstrated that body mass index correlates positively with mean and radial diffusivity in the fornix [28]. Moreover, in several psychiatric diseases (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of 21 BBS patients showed statistically significant increased CSF volume in both the surface of the brain and in the ventricles [14]. BBS is caused by at least 17 genes, which, when individually mutated, give rise to common phenotypes [[13,15-18]; and references therein].…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Several studies have reported the occurrence of hydrocephalus and a reduction in hippocampal volume in patients with BBS, defects that are also seen in several mouse models of BBS. 2531 …”
Section: Neurological Involvement In Ciliopathiesmentioning
confidence: 99%